High-Dose Ifosfamide Chemotherapy in a Series of Patients Affected by Myxoid Liposarcoma. (30th August 2017) - Colia, Vittoria; Fumagalli, Elena; Provenzano, Salvatore; Bertulli, Rossella; Stacchiotti, Silvia; Morosi, Carlo; Collini, Paola; Gronchi, Alessandro; Casali, Paolo G.; Sanfilippo, Roberta
Abstract : Background . To report on the activity of high-dose prolonged-infusion ifosfamide (HDIFX) chemotherapy in a retrospective series of patients affected by myxoid liposarcoma treated at Fondazione IRCCS Istituto Nazionale dei Tumori in Milan, Italy. Patients and Methods . Patients with an advanced myxoid liposarcoma treated with HDIFX (14 g/sqm, i.v., prolonged infusion of 14 days every 28 days) as a single agent between May 2002 and April 2017 were retrospectively reviewed. All pathologic diagnoses were centrally reviewed and molecularly confirmed. Response was evaluated by RECIST, and survival functions were computed by the Kaplan-Meier method. Results . Eleven patients with advanced myxoid liposarcoma were treated with HDIFX (male/female = 9/2, median age 33 years, range 31–75). Among these, 1/11 received HDIFX in first line, 5/11 in second line, 3/11 in third line, and 2/11 in fourth line for a median course number of 3 (range 2–7). No RECIST objective responses were observed. Overall median progression-free survival was 1, 9 months. Median overall survival was 37 months. At a median follow-up of 115 months, 1 patient is alive. Conclusions . In this series of patients affected by advanced myxoid liposarcoma, chemotherapy with HDIFX was essentially inactive.